Effect of lanthanum doping on modulating the thermochromic properties of VO2 thin films. Issue 54 (17th May 2016) - Wang, Ning; Chew Shun, Nigel Tan; Duchamp, Martial; Dunin-Borkowski, Rafal E.; Li, Zhong; Long, Yi
Abstract : La doping is found to be effective for enhancing the luminous transmission and solar modulating abilities simultaneously for VO2 thin films, and they exhibit a low τ c reducing rate of −1.1 °C per at%. Abstract : Lanthanum (La) doped vanadium dioxide (VO2 ) thin films were fabricated through a facile sol–gel technique. The La doping was found to be effective for reducing the phase transition temperature ( τ c ) of VO2 below the 4 at% doping level, with a reducing rate of −1.1 °C per at%. In addition, below the 3 at% La doping level, the band gap ( E g ) decreased steadily with the increasing addition of La dopants. 5 at% La doping can enhance both the integrated visible transmission ( T lum ) and the solar modulating ability (Δ T sol ) simultaneously. The combination of T lum = 50.1% and Δ T sol = 10.3% represents the best values for VO2 continuous thin films.